2020
DOI: 10.1016/j.actamat.2020.08.064
|View full text |Cite
|
Sign up to set email alerts
|

In-situ TEM study of irradiation-induced damage mechanisms in monoclinic-ZrO2

Abstract: We have investigated the microstructural and crystallographic evolution of nanocrystalline zirconia under heavy ion irradiation using in-situ transmission electron microscopy (TEM) and have studied the atomic configurations of defect clusters using aberration-corrected scanning transmission electron microscopy (STEM). Under heavy ion irradiation the monoclinic-ZrO2 is observed to transform into cubic phase, stabilised by the strain induced by irradiationinduced defect clusters. We suggest that the monoclinic-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…As a rule, the processes of phase transformation into ZrO 2 occur as a result of temperature heating or mechanical action, followed by the formation of solid solutions. At the same time, in some cases of practical application polymorphic transformations are used for so-called transformational hardening caused by stabilization of high-temperature phases [11,12]. The result of this process is a significant increase in the strength and fracture toughness of ceramics, which makes these materials promising in the field of mechanical engineering and reactor engineering.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, the processes of phase transformation into ZrO 2 occur as a result of temperature heating or mechanical action, followed by the formation of solid solutions. At the same time, in some cases of practical application polymorphic transformations are used for so-called transformational hardening caused by stabilization of high-temperature phases [11,12]. The result of this process is a significant increase in the strength and fracture toughness of ceramics, which makes these materials promising in the field of mechanical engineering and reactor engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The first large crater at 30 kV and 65 nA, a designed size at 30 kV and 1.0 nA, and final reducing tapering at 5 kV and 13 pA. TEM cross-sections of the as-fabricated CZ/Al composites and micro-pillars were prepared via FIB lift-out methodology (with a thickness of 50–200 nm). After the last step for thinning the specimen, the parameters of 5 kV and 48 pA were set to remove potential Pt, Ga +, and avoid irradiation-induced phase transformation in zirconia 43 45 . Each time before TEM observation, it was cleaned by an argon ion polisher (Fischione, Model 1040 NanoMill) with a milling voltage of 500 eV and milling current of 100 μA (at a tilt angle of ±10° and milling time of 30 mins each side), to remove the residual defective surface layer on the specimen, as a result of oxidation and Pt/Ga + implantation.…”
Section: Methodsmentioning
confidence: 99%
“…Any material that can be made into a TEM specimen can be studied during in situ ion bombardment including metals, [30][31][32][33][34][35][36][37][38][39][40] nanoparticle systems, 38,41,42 and ceramics. [43][44][45] These facilities and the subsequent studies have demonstrated the potential benefit of nanostructure materials to engineer radiation tolerance. 46,47 Figure 4 displays the power of in situ TEM studies which allow, for example, the continuous monitoring of crystal order and disorder at oxide interfaces, 48 and visualization of irradiationinduced dislocation loop motion in Cu.…”
Section: Electron and Positron Beam Characterization Techniquesmentioning
confidence: 97%